Peculiarities of the influence of the electoral properties of candidates on voting behavior of voters - I. V. Groshev; A. V. Gorbenko; I. V. Antonenko; V. N. Voronin (Вестник университета, 2019)
The problem of impact resistant and variables of electoral properties of candidates for for voting behavior of voters. In particular, it is shown that all factors determining the voting behavior of voters are graded on a fi ed (internal), weakly dependent on agitation characteristics and properties and external candidates voting factors of choice are highly dependent on the impact of social and communication activities of election campaigns has been presented. The classification of models of electoral behavior of voters, the structure of its determination. The author’s defi tion of electoral candidate properties, including objective-personal and socio-political attributes through subjective reflection electorate gradually form a holistic perception of the candidate, thereby defining his image in the mind of the voter, which is the end product of the electoral impact of candidate properties for the target audience during campaigning has be given.